Etude et simulations des fibres optiques à cristaux photoniques - Benguit Aicha; Senouci Rokaia; SONNE Abdelkader (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2022)
Photonic crystal fibres (PCF) represent a new class of optical waveguides that possess novel optical characteristics. PCFs have a number of degrees of freedom which is greater in importance than conventional fibres. In fact, the optical properties of these fibres are adjustable, resulting in a multitude of potential applications. Hence the interest in these fibres in particular in the field of telecommunications. In our work, we were interested in the characterization of the optical properties of PCFs by studying the impact of geometric deformations on the confinement losses and birefringence. The finite element method has been adopted for the analysis of structures.
OPTION : RESEAUX ET TELECOMMUNICATIONS